Physiological Changes, Activity, and Stress During a 100-km–24-h Walking-March - Jörres, Marc; Gunga, Hanns-Christian; Steinach, Mathias (Frontiers in Physiology, 2021)
Background: Long endurance exercises like ultramarathons are known to elicit various metabolic and physiological changes in the human body. However, little is known about very long duration exercise at low intensities regarding healthy human subjects. Aim: The purpose of this study was to evaluate changes in body composition and metabolism in long endurance but low intensity events. Methods: 25 male and 18 female healthy participants (age 34.6 ± 8.8 years; BMI: 22.4 ± 2.0 kg/m²) of the “100 km Mammutmarsch” were recruited for participation during the events in 2014 to 2016. Participants were required to walk but not run or jog. It was expected to complete the 100 km distance within 24 hours, resulting in a calculated mean speed of 4.17 km/h, which fits to the mean speed observed (4.12 ± 0.76 km/h). As not all participants reached the finish line, comparison of finishers (FIN, n=11) and non-finishers (NON, n=21), allowed differential assessment of performance. Body composition measured through BIA was determined pre and post event, blood samples were taken pre event, at 30 km, 70 km and 100 km. 19 participants wore Actimeter Armbands (SenseWear®) to gain information about body activity. Results: We found significant elevations for muscle and cardiac stress markers (CRP, CK, CK-MB, AST, ALT, cortisol and NT-pro-BNP) as well as decreasing markers of lipid metabolism (cholesterol, triglycerides, LDL). Although the intensity level demanded from our participants was low compared to other studies on marathons and ultramarathons, the alteration of tested parameters was similar to those of high intensity exercise. Besides duration of low intensity exercise, age, BMI and sex are relevant parameters that influence the elevation of stress factors. Notably, our data indicate that NT-pro-BNP might be a marker for cardiovascular fitness also in healthy adults. Conclusion: This low intensity long endurance walk evoked a strong systemic reaction because of large cell stress, also triggering shifts to a favourable lipid profile, comparable to higher intensity events. Despite increasing cardiac stress parameters, there were no indications of cardiac cell damage. Remarkably, the duration seems to have a greater influence on stress markers and metabolism than intensity.